Synthesis of new M-layer solid-solution 312 MAX phases (Ta1−xTix)3AlC2 (x = 0.4, 0.62, 0.75, 0.91 or 0.95), and their corresponding MXenes. Issue 5 (13th January 2021) - Rigby-Bell, Maxwell T. P.; Natu, Varun; Sokol, Maxim; Kelly, Daniel J.; Hopkinson, David G.; Zou, Yichao; Bird, James R. T.; Evitts, Lee J.; Smith, Matt; Race, Christopher P.; Frankel, Philipp; Haigh, Sarah J.; et al.
Abstract : Synthesis of a new solid solution (Ta, Ti)3 C2 T x MXene from the new quaternary (Ta, Ti)3 AlC2 MAX phase system, with variable Ti : Ta ratios, has been demonstrated. Abstract : Quaternary MAX phases, (Ta1− x Ti x )3 AlC2 ( x = 0.4, 0.62, 0.75, 0.91 or 0.95), have been synthesised via pressureless sintering of TaC, TiC, Ti and Al powders. Via chemical etching of the Al layers, (Ta0.38 Ti0.62 )3 C2 T z – a new MXene, has also been synthesised. All materials contain an M-layer solid solution of Ta and Ti, with a variable Ta concentration, paving the way for the synthesis of a range of alloyed (Ta, Ti)3 C2 T z MXenes with tuneable compositions for a wide range of potential applications.